The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1371/journal.pone.0018633
|View full text |Cite
|
Sign up to set email alerts
|

Ibudilast, a Pharmacologic Phosphodiesterase Inhibitor, Prevents Human Immunodeficiency Virus-1 Tat-Mediated Activation of Microglial Cells

Abstract: Human Immunodeficiency Virus-1 (HIV-1)-associated neurocognitive disorders (HAND) occur, in part, due to the inflammatory response to viral proteins, such as the HIV-1 transactivator of transcription (Tat), in the central nervous system (CNS). Given the need for novel adjunctive therapies for HAND, we hypothesized that ibudilast would inhibit Tat-induced excess production of pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNFα) in microglial cells. Ibudilast is a non-selective cyclic AMP phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 95 publications
1
26
0
Order By: Relevance
“…3E,F). Our data agrees with previously published data by others showing an inhibition of inflammatory responses and an increase in anti-inflammatory responses by AV411 [4245]. …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…3E,F). Our data agrees with previously published data by others showing an inhibition of inflammatory responses and an increase in anti-inflammatory responses by AV411 [4245]. …”
Section: Resultssupporting
confidence: 94%
“…It has been reported that AV411 can disrupt transcriptional activity of NF-ĸB and the stability of IκBα [42]. In an effort to explain how AV411 diminished MIF and TNF-α induced release by Tat ± morphine treatment, degradation of IκBα and nuclear translocation of NF-κB were determined by western blotting analysis (data not shown), and tracked by immunofluorescence labeling (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown the potential of this drug in reducing neuroinflammation in a number of neurological conditions such as relapsing-remitting multiple sclerosis (Barkhof et al, 2010), Tat-induced neurotoxicity (Kiebala and Maggirwar, 2011), potentiation of opioid analgesia (Hutchinson et al, 2009), and attenuation of methamphetamine-taking and relapse in animal models (Beardsley et al, 2010;Snider et al, 2013). At present, it is unknown how ibudilast impacts the synapse-a key structure involved in neurotransmission and neuroplasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis of cell populations expressing PDE4B2 after endotoxin injection revealed that microglia, astrocytes and endothelial cells showed the highest expression of PDE4B2 [195]. Notably, PDE4 specific inhibitor Rolipram has been demonstrated to significantly attenuate microglial activation in response to various stimuli, including endotoxin in several studies [191,[204][205][206][207]. These studies indicate a critical role of PDE4B in glial cell activation.…”
Section: Alcohol-induced Neuro-inflammation: Role Of Pde4 and Cammentioning
confidence: 89%